NFLUENCE OF BIOACOUSTIC STIMULATION OF THE RESPIRATORY SYSTEM OF SPORTSMEN ON LIFE-CAPACITY OF LUNGS - G. G. Erofeev (Исследования и практика в медицине)
Purpose. To study the influence of bioacoustic stimulation of the respiratory system in athletes on the value of vital capacity of the lungs.Materials and methods. For technical realization of bioacoustics stimulation of the respiratory system, a biotechnical system, containing a block of an acoustic interferometer, an interferometer control system, and a system for recording sound field parameters, was used. The study involved nine athletes test volunteers: men aged 19 to 31 years, a sport – skiing, a sports category – the first adult, who underwent a training using bioacoustics stimulation in the following way: three times for three minutes each exposure, with an interval between exposures equal to one minute. Before the beginning of each exposure, the medical staff conducted a survey of the athlete’s well-being, measurement of the heart rate and blood saturation with oxygen, and determination of the vital capacity of the lungs. During the exposure, a constant control of health, heart rate and blood saturation with oxygen was conducted, and measurements of the vital capacity of the lungs were carried out after each stimulating effect.Results. Eight of the nine volunteers increased the vital capacity of the lungs, according to subjective sensations, all volunteers noted a feeling of deeper breaths after exposure, a feeling of lightness of breath and absence of shortness of breath after training afterwards. Athletes who participated in earlier stages of the study noted that the effect of stimulation is pronounced in terms of subjective assessments of a feeling of lightness of breath, a greater depth of inspiration, a greater volume of breathing at once, and within 3 days after three-fold exposure during one session. Conclusion. The results of the study testify to the significant potential possibilities of bioacoustics stimulation of the respiratory system of athletes to increase the functional reserves of the body, determined by the increase in the vital capacity of the lungs. Important for the practice of sports medicine is that the increase in vital capacity of the lungs occurs after a one-day course of bioacoustics stimulation of the respiratory system, persists for 3 or more days after stimulation and is accompanied by subjective estimates of easier breathing.